Prestorage High CO2 and 1-MCP Treatment Reduce Chilling Injury, Prolong Storability, and Maintain Sensory Qualities and Antioxidant Activities of “Madoka” Peach Fruit - Tilahun, Shimeles; Jeong, Min Jae; Choi, Han Ryul; Baek, Min Woo; Hong, Jin Sung; Jeong, Cheon Soon (Frontiers in Nutrition, 2022)
Cold storage is widely used to prolong the storability of peach fruit. However, prolonged storage at low temperatures results in chilling injury (CI) in some susceptible peach cultivars during or after cold storage. Prestorage high CO2 and 1-methylcyclopropene (1-MCP) treatments are among the methods reported to alleviate CI and maintain the firmness of peach fruit. Hence, this study investigated CI, ripening-related physicochemical parameters, sensory qualities, total phenolics and flavonoids, and antioxidant activities of “Madoka” peach fruit to observe the effectiveness of prestorage treatment with high CO2 and 1-MCP during the storage at 0 and 5°C. Based on the CI index, control fruits were acceptable for marketing up to 20 and 16 days of storage at 0 and 5°C, respectively, while the treated fruits could be marketable up to 28 days of storage. The results of firmness and firmness-related parameters [pectin content and polygalacturonase (PG) activity] also revealed that both high CO2 and 1-MCP treatments were effective in delaying the ripening process of Madoka peach, and the storage at 0°C showed better results than at 5°C. However, based on the overall sensory evaluation results, the treated and control fruits were acceptable for marketing up to 20 and 12 days of storage, respectively, in both storage conditions. After deciding on fruit marketability based on the combined objective postharvest quality parameters and subjective sensory qualities, we analyzed the changes in total phenolics, flavonoids, and antioxidant activities at harvest, on the 12 and 20th days of cold storage. Storage of Madoka peach at 0°C maintained total phenolics, flavonoids, and antioxidant activities regardless of prestorage treatment with high CO2 and 1-MCP. In summary, storing Madoka peach fruit at 0°C after treating it with 30% CO2 for 6 h or 0.5 μl L–1 1-MCP for 24 h reduces CI, prolongs storability, and maintains sensory quality and antioxidant properties.